Cooperación internacional en ciencia, tecnología e innovación entre Brasil y Colombia durante los gobiernos Lula da Silva (2003 - 2010) - Suárez Romero, Ana María [UNESP] (2015)
Relationships between Brazil and Colombia have focused on strengthening the processes of regional integration through decisions aimed to increase the cooperation between the two countries and strengthen their links due to its vicinity. Issues related to security cooperation, increase in trade and investment, border issues, aeronautical industries, police cooperation in education and research, technical assistance, bioenergy and biofuels have been fundamental parts of the bilateral agenda allowing the consolidation of alliances between the two countries. The objective of this work is to characterize the mechanisms and instruments of the international cooperation in science, technology and innovation (CT+I) implemented between the Brazilian and Colombian research and development institutions during the government of president Luiz Inácio Lula da Silva (2003-2006/2007-2010) in order to analyze the bilateral relations and establish how Colombian external policies implemented on the study period influenced the international cooperation in CT+I with Brazil.